2019
DOI: 10.1186/s12875-018-0895-2
|View full text |Cite
|
Sign up to set email alerts
|

Communication, continuity and coordination of care are the most important patients' values for family medicine in a fee-for-services health system

Abstract: BackgroundRepresenting 60% of medical consultations in Switzerland, primary care holds an important place in our medical system. Patients’ values in family medicine (FM) are nowadays recognized as important factors to take into account in order to provide good quality of care. The aim of this study is to describe patients’ most important values regarding FM and to assess their associations with socio-demographics factors in a fee-for-services health system.MethodsWe analyzed the Swiss 2012 study on Quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 13 publications
5
35
0
Order By: Relevance
“…In our study, the clear majority of items reaching the 90% limit in all countries were in the communication-domain (six of 15 items in this domain reached the limit). This corresponds with a study of Swiss QUALICOPC data, where the authors concluded that items related to communication/patient-centeredness and coordination/continuity of care were rated as more important than items related to access (17). In the Europep study from 1999 performed in eight countries including Norway, Sweden and Denmark, only two items regarding accessibility reached the top-ten list regarding importance (quick access in case of emergencies (ranked second) and it should be possible to make an appointment at short notice (ranked sixth)) (6).…”
Section: Discussionsupporting
confidence: 85%
“…In our study, the clear majority of items reaching the 90% limit in all countries were in the communication-domain (six of 15 items in this domain reached the limit). This corresponds with a study of Swiss QUALICOPC data, where the authors concluded that items related to communication/patient-centeredness and coordination/continuity of care were rated as more important than items related to access (17). In the Europep study from 1999 performed in eight countries including Norway, Sweden and Denmark, only two items regarding accessibility reached the top-ten list regarding importance (quick access in case of emergencies (ranked second) and it should be possible to make an appointment at short notice (ranked sixth)) (6).…”
Section: Discussionsupporting
confidence: 85%
“…Polish patients ranked elements of their commitment to the consultation as less essential. In Switzerland, items related to patients' activation were generally declared as "very important" by less than 50% of patients [26]. Patient-involvement in decision-making with regards to their treatment plans was scored moderately in Greek data [25].…”
Section: Findings In Light Of Other Studiesmentioning
confidence: 99%
“…Patients want professionals who are both interested and sympathetic and provide them with sufficient time and attention [24]. Other QUALI-COPC participative countries like Greece and Switzerland also reported the importance of the patientphysician relationship during consultations [25,26]. The less important patient expectations also showed similarities internationally.…”
Section: Findings In Light Of Other Studiesmentioning
confidence: 99%
“…Older age was found to diminish risk of negative experiences in all the dimensions, similar to a good doctor-patient relationship [40]. Similarly, Droz et al [41] obtained results among Norwegian patients, and the highest assessment was given to coordination, continuity, and communication. The last two have a close relationship with presence of chronic diseases.…”
Section: Discussionmentioning
confidence: 82%